ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ONLINE SHOP KONSUMEN (STUDI KASUS PADA MAHASISWA DI UNIVERSITAS ISLAM INDONESIA) - Rizal Ardiansyah (Journal Competency of Business, 2019)
This empirical research is intended to determine the effect of financial risk, product risk, convenience risk, non-delivery risk, infrastructure variables, and return policy on consumer attitudes, to determine the effect of attitudes on consumer online shop buying interest, to determine the effect of financial risk, product risk. , convenience risk, non-delivery risk, infrastructure variables, return policy, and attitudes towards consumers 'online shop buying interest, to determine the influence of consumer behavior factors which are the most dominant in influencing consumers' online shop buying interest. The object of this research is the students of the Islamic University of Indonesia using 96 active student respondents as the research sample. Data analysis used Multiple Regression Analysis using a data processing program, namely SPSS for Windows Release 17.00. Based on the results of the analysis shows that there is a significant influence between financial risk, product risk, convenience risk, non-delivery risk, return policy, and infrastructure on online shopping attitudes, the product risk dimension has a dominant influence on online shopping attitudes, there is a significant influence between online shopping attitudes. With buying interest, there is a significant influence between the risk and attitude of online shopping on consumer buying interest and the dimensions of online shopping attitudes have a dominant influence on consumer buying interest.